Integrative and Complementary Practices in undergraduate Dentistry: a Qualitative Study (Research, Society and Development, 2022)
The objective was to understand the perception of students of the Extension Project "Complementary Integrative Practices in Health: Acupuncture in Dentistry", from the Faculty of Dentistry of the Federal University of Minas Gerais in 2019. Qualitative research, with graduate students as the study population and collection of data by focus group. The interpretation of the speeches was conducted by content analysis, based on the National Curriculum Guidelines, with three themes emerging: prior knowledge about the complementary therapies; contribution of complementary therapies to dentistry; humanization of care. There is a superficial knowledge of the subject, but interest in knowing it. There was a need to encourage the study of complementary therapies in undergraduate courses, as they are rarely addressed in health education and there is interest from students. They considered that complementary therapies are positive for dentistry, have good habits and low risk; they are in line with the regulations and demands that already exist in the SUS and expand the area of professional activity. It was concluded that the complementary therapies are incipient in graduation, have benefits for dentistry reflected in the scientific literature and clinical practice and are in line with the precepts defined in the National Curriculum Guidelines, providing the patient with full and humanized care.